Amino Acid Substitutions HA A150V, PA A343T, and PB2 E627K Increase the Virulence of H5N6 Influenza Virus in Mice - Peng, Xiuming; Liu, Fumin; Wu, Haibo; Peng, Xiaorong; Xu, Yufan; Wang, Liyan; Chen, Bin; Sun, Tao; Yang, Fan; Ji, Shujing; Wu, Nanping (Frontiers in Microbiology, 2018)
Abstract H5N6 avian influenza viruses (AIVs) can cause severe pneumonia and death in humans. However, the molecular determinants of H5N6 influenza virus mammalian adaption are still unclear. Three amino acid substitutions (HA A150V, PA A343T, PB2 E627K) are observed in H5N6 virus A/duck/Zhejiang/6D2/2013 (6D2) in lung-to-lung passage in mice. These substitutions are crucial to the pathogenicity of mouse-adapted virus. In this study, we investigated the contribution of each amino acid substitution in the virus by reverse genetics. The results demonstrate that HA A150V greatly altered the receptor binding preference of 6D2. Virus bearing this substitution acquired increased mortality than mice infected with wild-type 6D2. The PA A343T substitution mildly enhanced viral polymerase activity but the reduced survival rate in mice indicates this substitution may change the immunoreaction of the host. The well-known PB2 E627K substitution increased 8 folds the relative polymerase activity compared to PA A343T and resulted in 100% death rate in mice. In addition, we show that PA A343T dramatically exacerbates the effect of PB2 E627K on viral polymerase activity; when combined, these two substitutions work synergistically. However, HA A150V and PA A343T seemed to attenuate PB2 E627K in vivo, which implies the difference between mixed viral populations under natural condition and single population under experiment, specialization and cooperation in quasispecies is important in the process of adaption. This study suggests that HA A150V, PA A343T, and PB2 E627K are crucial in the adaption and increased pathogenicity of H5N6 in mammalian hosts.